The Internalization of Sufi Values in the Tapak Suci Pencak Silat Tradition as a Medium of Cultural Da'wah in the Palembang Community - Mubin, Shihabum; Purwanto, Agus; Munir, Munir; Torik, Muhammad; Alimron, Alimron (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This study aims to analyze the process of internalizing Sufi values within the Tapak Suci pencak silat tradition as a medium for cultural da’wah in the community of Palembang City, South Sumatra. In Muslim communities, the pencak silat tradition functions not only as a self-defense activity but also as a space for transmitting Islamic spiritual and ethical values in shaping religious character. This study employs a qualitative approach with an ethnographic research design. The research was conducted at several Tapak Suci training centers in Palembang. Data were collected through participant observation, in-depth interviews with instructors, silat school members, and community leaders, as well as documentary analysis. Data analysis employed an interactive analysis model encompassing data reduction, data presentation, and conclusion drawing/verification. The results indicate that the internalization of Sufi values within the Tapak Suci tradition occurs through spiritual training practices such as reciting prayers before and after training, zikr, instilling etiquette, training discipline, and the exemplary role of instructors as moral and spiritual figures. These practices form a process of cultural da’wah that unfolds persuasively and contextually through cultural activities deeply rooted in community life. In addition to serving as a medium for physical training, this tradition also contributes to the formation of religious character, social solidarity, and spiritual awareness among its members. The novelty of this study lies in the integrative analysis of Sufi values and pencak silat practices as a medium for cultural da’wah, affirming local martial arts traditions as an effective culture-based da’wah model in strengthening spirituality and Islamic identity within the community.